2010
DOI: 10.1063/1.3435477
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Meyer–Neldel energy on energetic disorder in organic field effect transistors

Abstract: Articles you may be interested inInfluence of device geometry in the electrical behavior of all organic ambipolar field effect transistors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 14 publications
4
44
1
Order By: Relevance
“…27 We note that if hopping transport occurs in an OSC for which complexities such as carrier percolation along grain boundaries exist, the derived hopping parameters will represent effective values which depend to some extent on film morphology; for example, samples with smaller grain size and hence larger disorder may be expected to have a larger DOS width. 23 However, an isotropic hopping model with a regular cubic lattice such as the one assumed here has successfully described transport in many small molecular 23,35 and conjugated polymer [4][5][6] OSCs. Dopant type is known to have a strong effect on transport in PEDOT, as evidenced by recent observations in which the maximum thermoelectric power factor (S 2 σ ) was found to increase from 6.0 × 10 −6 W/mK 2 when doped with poly(styrenesulfonate) (Pss) 36 to 3.24 × 10 −4 W/mK 2 when doped with tosylate (Tos) [ Fig.…”
Section: Comparison With Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…27 We note that if hopping transport occurs in an OSC for which complexities such as carrier percolation along grain boundaries exist, the derived hopping parameters will represent effective values which depend to some extent on film morphology; for example, samples with smaller grain size and hence larger disorder may be expected to have a larger DOS width. 23 However, an isotropic hopping model with a regular cubic lattice such as the one assumed here has successfully described transport in many small molecular 23,35 and conjugated polymer [4][5][6] OSCs. Dopant type is known to have a strong effect on transport in PEDOT, as evidenced by recent observations in which the maximum thermoelectric power factor (S 2 σ ) was found to increase from 6.0 × 10 −6 W/mK 2 when doped with poly(styrenesulfonate) (Pss) 36 to 3.24 × 10 −4 W/mK 2 when doped with tosylate (Tos) [ Fig.…”
Section: Comparison With Experimental Datamentioning
confidence: 99%
“…23 To approximate the effect of dopant volume, which increases hopping distance and thereby exponentially decreases the transition rate, we introduce a total DOS N t that depends on the dopant concentration (n d ):…”
mentioning
confidence: 99%
“…We recently studied both experimentally and theoretically the MN effect in C 60 OFETs and have shown that the characteristic parameter called MN energy "E MN = kT MN " is determined by the width of the densityof-state ͑DOS͒ distribution, , in the conductive channel of an organic semiconducting film. [4][5][6] Measurements of the MN effect in C 60 films grown at different conditions have revealed a significant shift in the MN energy ͑and consequently change in the energetic disorder parameter ͒ with changing film morphology. 5 Thus it was proposed 5 that "E MN " can be used as an important material characterizing parameter for active organic semiconductor layers in OFETs independent of the device geometry.…”
Section: Effect Of Source-drain Electric Field On the Meyer-neldel Enmentioning
confidence: 99%
“…[4][5][6] Measurements of the MN effect in C 60 films grown at different conditions have revealed a significant shift in the MN energy ͑and consequently change in the energetic disorder parameter ͒ with changing film morphology. 5 Thus it was proposed 5 that "E MN " can be used as an important material characterizing parameter for active organic semiconductor layers in OFETs independent of the device geometry.…”
Section: Effect Of Source-drain Electric Field On the Meyer-neldel Enmentioning
confidence: 99%
“…The E a , e 0 , and carrier concentration effects have been observed in fullerene C 60 films by using a C 60 -based field effect transistor (FET). 8,10,29,32 The E a increases and r decreases with increasing electric field. Also, the mobility increases with increasing the carrier concentration adjusted using the gate voltage.…”
Section: Resultsmentioning
confidence: 99%